Pengaruh Budaya Organisasi Terhadap Kinerja Korporasi Pada PT. Pendidikan Maritim dan Logistik Indonesia - Agustin, Silvya; Syahrinullah, Syahrinullah (LPPM Universitas Muhammadiyah Mamuju, 2022)
The culture applied at PT Pendidikan Maritim dan Logistik Indonesia is LAKHLAK which is the crononym c of Trustworthy, Competent, Charmonic, Loyal, Adaptive, and Collaborative. ENDs are set as the basic values ​​that are mandatory for all BUMN holders in carrying out their daily business and activities because the government wants the process of transforming BUMN to be carried out thoroughly to every element of human resources (HR) in it. The aim of this research is to identify and analyze the influence of organizational culture on corporate performance in PT.cl Indonesia's Maritime and Logistics Education. Cinic research uses qualitative methods, then, the data set obtained during observations or interviews is selected something that is interesting, fresh, and updated. the results of the study found that there was a positive influence from organizational culture on corporate performance at PT. Indonesian Maritime and Logistics Education.